Invasiveness of decompression surgery affects modeled lumbar spine kinetics in patients with degenerative spondylolisthesis - Kosterhon, M.; Müller, A.; Rockenfeller, R.; Aiyangar, A. K.; Gruber, K.; Ringel, F.; Kantelhardt, S. R. (Frontiers in Bioengineering and Biotechnology, 2024)
The surgical treatment of degenerative spondylolisthesis with accompanying spinal stenosis focusses mainly on decompression of the spinal canal with or without additional fusion by means of a dorsal spondylodesis. Currently, one main decision criteria for additional fusion is the presence of instability in flexion and extension X-rays. In cases of mild and stable spondylolisthesis, the optimal treatment remains a subject of ongoing debate. There exist different opinions on whether performing a fusion directly together with the decompression has a potential benefit for patients or constitutes an overtreatment. As X-ray images do not provide any information about internal biomechanically forces, computer simulation of individual patients might be a tool to gain a set of new decision criteria for those cases. To evaluate the biomechanical effects resulting from different decompression techniques we developed a lumbar spine model using forward dynamic-based multibody simulation (FD_MBS). Preoperative CT data of 15 patients with degenerative spondylolisthesis at the level L4/5 who underwent spinal decompression were identified retrospectively. Based on the segmented vertebrae 15 individualized models were built. To establish a reference for comparison, we simulated a standardized flexion movement (intact) for each model. Subsequently, we performed virtual unilateral and bilateral interlaminar fenestration (ILF) and laminectomy (LAM) by removing the respective ligaments in each model. Afterwards, the standardized flexion movement was simulated again for each case and decompression method, allowing us to compare the outcomes with the reference. This comprehensive approach enables us to assess the biomechanical implications of different surgical approaches and gain valuable insights into their effects on lumbar spine's functionality. Our findings reveal significant changes in the biomechanics of vertebrae and intervertebral discs (IVDs) as a result of different decompression techniques. As the invasiveness of decompression increases, the torque transmitted on the vertebrae significantly rises, following the sequence: intact ➝ ILF (unilateral) ➝ ILF (bilateral) ➝ LAM. Conversely, we observed a reduction in anterior-posterior shear forces within the IVDs at the level L3/L4 and L4/L5 following LAM. Our findings showed that it was feasible to forecast lumbar spine kinematics after three distinct decompression methods which might be helpful in future clinical applications.